Evaluasi Sistem Informasi Akuntansi Pembelian Dalam Kaitannya Dengan Pengendalian Internal - Roup, Abdul (Institut Bisnis dan Informatika Kesatuan, 2019)
The purpose of this research is to study the accounting information system and internal control in assisting the purchasing activities. The research was administered in PT Jayatama Selaras located in Kawasan Korin Jl. Raya Narogong, Kabupaten Bogor 16820, Indonesia. Internal control is impeccably necessary for working entities due to its functions in supporting and assisting companies to protect their cash and assets. Internal control also protects companies from frauds committed by irresponsible individuals and causing great loss. The research method used is descriptive qualitative where the author described the system and procedures of purchasing activities and internal control run and operated in PT Jayatama Selara, and then compared them to literature explanations. The study resulted in conclusion that PT Jayatama Selaras has already been running and operating an appropriate system in which the company is not allowed to having single supplier. There is gradual approval in the process of request until purchasing decision, and there are also task divisions in the departments of warehouse, purchasing, accounting and receiving. Internal audit is consistently being carried out twice a year.